KUALITAS TIDUR PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Dian Anggraini; Dewi Marfuah; Susy Puspasari (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2020)
Background : In the last five years, the prevalence of breast cancer in Indonesia has increased. The usual treatment for breast cancer is chemotherapy, which can cause physical problems that affect sleep quality. Sleep disorders are often experienced by breast cancer patients, where the impact affects the healing of the cancer and the immune system so that the condition and immune system cannot be maintained optimally in repairing body cells. Purpose: to determine the quality of sleep in breast cancer patients undergoing chemotherapy and to see which components have contributed to disturbing sleep quality. Methods: The study used a quantitative descriptive approach. Sampling technique accidental sampling with 100 respondent. The questionnaire used to measure sleep quality was the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data analysis technique used univariate analysis, there are two interpretations on the PSQI. Sleep quality is good if the score is ≤ 5, sleep quality is bad if the score is> 5. Results: Most of the respondents have poor sleep quality. This research is expected to increase the role of nursing care and educator so that it can improve the quality of life of breast cancer patients undergoing chemotherapy